2016
DOI: 10.1038/ncomms11901
|View full text |Cite
|
Sign up to set email alerts
|

A broad analysis of resistance development in the malaria parasite

Abstract: Microbial resistance to chemotherapy has caused countless deaths where malaria is endemic. Chemotherapy may fail either due to pre-existing resistance or evolution of drug-resistant parasites. Here we use a diverse set of antimalarial compounds to investigate the acquisition of drug resistance and the degree of cross-resistance against common resistance alleles. We assess cross-resistance using a set of 15 parasite lines carrying resistance-conferring alleles in pfatp4, cytochrome bc1, pfcarl, pfdhod, pfcrt, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
121
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(124 citation statements)
references
References 39 publications
1
121
0
1
Order By: Relevance
“…Recent studies with compounds from the open-access Malaria Box [41] have identified several chemotypes against which resistance cannot be generated in the laboratory [42]. Attractive scaffolds from within this set will be prioritized for optimization and progress, and in parallel, target identification will be important.…”
Section: The Need To Prioritize Chemical Scaffolds and Combinations Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies with compounds from the open-access Malaria Box [41] have identified several chemotypes against which resistance cannot be generated in the laboratory [42]. Attractive scaffolds from within this set will be prioritized for optimization and progress, and in parallel, target identification will be important.…”
Section: The Need To Prioritize Chemical Scaffolds and Combinations Tmentioning
confidence: 99%
“…Other PfATP4 inhibitors are in development, with SJ733 (+−SJ00557733; [86, 87]) recently starting phase I studies. A concern with targeting PfATP4 is that mutations in this gene confer resistance against aminopyrazoles, dihydroisoquinolones and spiroindolones [42, 88, 89]. The developmental pathway could be to demonstrate safety and tolerability of a parenteral formulation whilst assessing activity in adults with moderately severe malaria (hyperparasitemic cases; [85]).…”
Section: Severe Malariamentioning
confidence: 99%
“…Longer-lasting drugs with similar modes of action might prove superior at reducing the risk of resistance. The rate of parasite killing is another important characteristic, with evidence showing that fast-acting antimalarials are less prone to yield resistance in vitro 131 . Resistance selection efforts have also proven unsuccessful with the potent antimalarial methylene blue that is active against the intra-erythrocytic asexual and gametocyte stages.…”
Section: Can We Design Drugs That Are ‘Resistance Proof’?mentioning
confidence: 99%
“…From there, Winzelers group applied the strategy to look at a variety of gene mutations conferring resistance in the malaria parasite, Plasmodium (2). Over time, theyve even moved the strategy into looking at clinical trial candidates.…”
Section: Tackling Targetsmentioning
confidence: 99%